2017
DOI: 10.1152/advan.00157.2016
|View full text |Cite
|
Sign up to set email alerts
|

Learning through debate during problem-based learning: an active learning strategy

Abstract: We explored medical student's views and perceptions of a series of debates conducted during problem-based learning (PBL) practiced as a part of the Spiral curriculum at the Imam Abdulrahman Bin Faisal University, Saudi Arabia. A series of debates were employed during PBL sessions for second-year female medical students, over the period 2014-2016. Each cohort of students was randomly split into 10 small PBL groups and exposed to weekly PBL activity. Within each group, the students were divided into a propositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 26 publications
8
67
0
2
Order By: Relevance
“…A key essential element of active learning is to actively engage students in deeper learning by fostering their ability to create new knowledge and apply the acquired knowledge and skills by demonstrating well-developed judgement and responsibility as learners (Ní Raghallaigh & Cunniffe, 2013). Moreover, research demonstrates that the use of an active learning methodology not only increases student engagement, but also improves student retention of material and subsequently develops students' critical thinking and problem-solving skills (Kvam, 2000;Mumtaz & Latif, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A key essential element of active learning is to actively engage students in deeper learning by fostering their ability to create new knowledge and apply the acquired knowledge and skills by demonstrating well-developed judgement and responsibility as learners (Ní Raghallaigh & Cunniffe, 2013). Moreover, research demonstrates that the use of an active learning methodology not only increases student engagement, but also improves student retention of material and subsequently develops students' critical thinking and problem-solving skills (Kvam, 2000;Mumtaz & Latif, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…First, they show the possibility of constructing a more efficient procedure to promote open-minded thought. Previous studies have reported several beneficial effects from a full set of debate practice tasks (Hall, 2011;Zare & Othman, 2013;Mumtaz & Latif, 2017). However, the full set of debate practice tasks requires many participants (e.g., debaters on both-sides and de-briefers) and enough practice time, including preparation and/or instruction periods.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that debate practice is an effective procedure for improving openminded thought, the neural underpinning behind changes in open-minded thought remains unclear. Previous studies have suggested some beneficial effects of debate practice including tolerance toward different viewpoints, analytic or communication abilities, self-confidence, and mastering the educational content (Miri, David, & Uri, 2007;Oros, 2007;Hall, 2011;Zare & Othman, 2013;Mumtaz & Latif, 2017). However, those results were based on post-hoc questionnaires or interviews that relied on participant introspection and, therefore, they provide no objective information on how participant mind-set is changed through CT practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, different strategies were proposed aiming the students' interaction and participation in the knowledge construction. Among these methodologies are the problem-based learning (PBL), team-based learning (TBL), among others [3,4]. But not always is possible to change from traditional curriculum to an all-active course, as required in PBL, for example, since it involves curricular and institutional modifications.…”
Section: Introductionmentioning
confidence: 99%